2018
DOI: 10.17559/tv-20160816155022
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Approach for Gob-Side Entry Retaining With Thick and Hard Roof: A Case Study

Abstract: An innovative roadway layout in a Chinese colliery based on gob-side entry retaining (GER) with thick and hard roof (THR) was introduced. Suspended roof is left with a large area in GER with THR, which leads to large area roof weighting (LARW). LARW for GER with THR and mechanism of shallow-hole blasting to force roof caving in GER were expounded. Key parameters of shallow-hole blasting to force roof caving are proposed. LS-DYNA3D was used to validate the rationality of those key parameters, and UDEC was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Based on numerous field practices in GER [ 10 , 16 , 17 ], it has been observed that: (i) The impact of the overlying strata beneath the primary key stratum on the main roof (sub-key stratum) is significantly more significant than that of roadway support; (ii) The construction of the filling body along gob side can only occur at a specific distance behind the working face and often faces challenges in achieving complete connection with the immediate roof. Its supportive role becomes effective only when there is a certain degree of roof subsidence, indicating its passive nature.…”
Section: Stability Analysis Of Main Roof During the Whole Ger Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on numerous field practices in GER [ 10 , 16 , 17 ], it has been observed that: (i) The impact of the overlying strata beneath the primary key stratum on the main roof (sub-key stratum) is significantly more significant than that of roadway support; (ii) The construction of the filling body along gob side can only occur at a specific distance behind the working face and often faces challenges in achieving complete connection with the immediate roof. Its supportive role becomes effective only when there is a certain degree of roof subsidence, indicating its passive nature.…”
Section: Stability Analysis Of Main Roof During the Whole Ger Processmentioning
confidence: 99%
“…Consequently, this will increase stability of the plastic solid coal rib [ 39 , 40 ]. Consider using early strength materials with rapid resistance increasing properties for constructing filling body [ 10 ]. By doing so, load sharing between filling body and solid coal rib can occur at an earlier stage.…”
Section: Stability Mechanism Of Plastic Solid Coal Rib In Deep Germentioning
confidence: 99%
See 1 more Smart Citation
“…The gob side entry retaining is the use of special materials in the roadway side to construct a roadway protection belt, the retained roadway to serve the next working face (Zhang et al, 2018;Zhao, 2019). The gob side entry retaining can realize the Y-type ventilation, effectively solve the problem of gas overrun in the upper corner, and realize gas pre-extraction of adjacent coal seams, which provides a guarantee for safe mining (Zhang and Li, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Coal is the main energy source in China, accounting for more than 60% of the energy consumption structure. In the past and over a long period of time, coal mining was characterized by high-intensity and extensive mining. In pursuit of production growth, a large number of high-quality coal resources have been abandoned and wasted, including the thin coal seam that is not mined in the process of multi-seam mining, the top coal that is left for roof protection in layered mining, and the top coal and bottom coal left in the process of medium thick coal mining, among others. Recovery of these coal resources can effectively improve the recovery rate and extend the service life of the mine. However, in the process of remining, the roof rocks that fall after the original coal seam is mined are compacted and cemented to form a regenerated roof .…”
Section: Introductionmentioning
confidence: 99%